NUMERICAL MODELLING ON BEHAVIOUR OF COLD-FORMED STEEL UNLIPPED CHANNEL UNDER COMBINED COMPRESSION AND BENDING ACTIONS - Tanjung Rahayu Raswitaningrum; Budiman Budiman; Basit Al Hanif; Sahrul Mujib (International Journal of Civil Engineering and Infrastructure, 2022)
Research and development of construction materials continue to be carried out, getting materials, cross-sectional shapes, and manufacturing methods that are more efficient than before. Cold-formed steel is a material breakthrough in construction that has advantages over hot-rolled steel. In this paper, the cross-section of cold-rolled steel unlipped channel will be analyzed which is subjected to a combination of axial and bending loads. Investigating elements will be carried out using the finite element method on ABAQUS, and the results of the analysis produce a visualization of the behavior and capacity of the cold-rolled steel section. The cross-section capacity results obtained from the numerical test results will be compared with the predictions given by SNI 7971-2013 or AS/NZS 4600. Existing research in the literature will be used as a reference in conducting numerical analysis and calculating ultimate capacities.